Identification of Antimicrobial Peptides Isolated From the Skin Mucus of African Catfish, Clarias gariepinus (Burchell, 1822) - Okella, Hedmon; Ikiriza, Hilda; Ochwo, Sylvester; Ajayi, Clement Olusoji; Ndekezi, Christian; Nkamwesiga, Joseph; Kaggwa, Bruhan; Aber, Jacqueline; Mtewa, Andrew Glory; Koffi, Tindo Kevin; Odongo, Steven; Vertommen, Didier; et al. (Frontiers in Microbiology, 2021)
Antimicrobial peptides (AMPs) constitute a broad range of bioactive compounds in diverse organisms, including fish. They are effector molecules for the innate immune response, against pathogens, tissue damage, and infections. Still, AMPs from African Catfish, Clarias gariepinus skin mucus are largely unexplored despite their possible therapeutic role in combating antimicrobial resistance. In this study, African Catfish Antimicrobial peptides (ACAPs) were identified from the skin mucus of African Catfish, C. gariepinus. Native peptides were extracted from fish mucus scrapings in 10% acetic acid (v/v) and ultra-filtered using 5kDa molecular cut-off membrane. The extract was purified using C18 Solid Phase Extraction. The antibacterial activity was determined using the Agar Well Diffusion method and broth-dilution method utilizing Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922). Thereafter, Sephadex G-25 gel filtration was further utilized in bio-guided isolation of the most active fractions prior to peptide identification using Orbitrap Fusion Lumos Tribrid Mass Spectrometry. The skin mucus extracted from African Catfish from all the three major lakes of Uganda exhibited antimicrobial activity on E. coli and S. aureus. Lake Albert’s C. gariepinus demonstrated the best activity with the lowest MIC of 2.84 µg/mL and 0.71 µg/mL on S. aureus and E. coli respectively. Sephadex G-25 peak I mass spectrometry analysis alongside in silico analysis revealed seven short peptides (11-15 amino acid residues) of high antimicrobial scores (0.561-0.905 units). In addition, these peptides had a low molecular weight (1005.57-1622.05 Da), and had percentage hydrophobicity above 54%. Up to four of these antimicrobial peptides demonstrated α-helix structure conformation, rendering them amphipathic. The ﬁndings of this study indicate that novel antimicrobial peptides can be sourced from the skin mucus of C. gariepinus. Such antimicrobial peptides are potential alternatives to traditional antibiotics and can be of great application to food and pharmaceutical industries; however, further studies are still needed to establish their drug-likeness and safety profiles.